first set the equation =0
8z^2-56z+48=0
now factor out 8
8(z^2-7z+6)=0
you can forget about the 8 and just set z^2-7z+6=0 and factor:
(z-1)(z-6)=
z-1=0
z=1
z-6=0
z=6
2007-06-07 13:47:00
·
answer #1
·
answered by Stop Sine 3
·
0⤊
0⤋
Rewrite this as 8z^2 - 56z + 48 = 0
You can factor out an 8 which will make things easier:
8(x^2 - 7z + 6) = 0
Now factor the rest. We have a - before the 6 and a minus before the 7z, so we need factors in the form of (z - ?)(z - ?). We just need two numbers whose product is 6 and sum is 7. The obvious ones are 1 and 6. This gives us:
8(x - 6)(x - 1) = 0
So x = 6, 1
2007-06-07 20:44:43
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
First, move all the terms to one side:
8z^2-56z+48=0
Next, divide both side by 8 and you get:
z^2-7z+6=0
The factors of 6 are 1 & 6 or 2 & 3. factoring yields:
(z-1)(z-6)=0 Therefore z = 1 or 6
2007-06-07 20:49:46
·
answer #3
·
answered by skibum1530 1
·
0⤊
0⤋
8z^2 - 56z + 48 = 0
dividing by 8 yields
z^2 - 7z + 6 = 0
Factoring:
(z-?)(z-?) = 0 (rule states that the second sign is positive when both factors have a minus sign; the first sign is negative, thus both signs must be negative)
(z-6)(z-1) = 0
(The only factorization of 6 that adds to 7 is 6 and 1).
Thus z = 1 or 6
2007-06-07 20:47:30
·
answer #4
·
answered by snjallaboutme 2
·
0⤊
0⤋
okay.. um... first of all you want to move all the terms to one side. so you subtract the 56z and add the 48 to the left to make 0 on the right. Okay.. then you will have 8z^2-56z+48=0 right?... Okay.. the easiest thing to do is to divide all the terms, even 0, by 8, the least common multiple. so you will get z^2-7z+6=0. now the problem doesnt look as scary as it did before right? then you factor... you get (z-6) (z-1)=0. therefore.. z=6 and 1. if you have any questions.. feel free to email me at mashi_cutie@hotmail.com
2007-06-07 20:48:56
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
8 z² - 56z + 48 = 0
Divide thru by 8
z² - 7z + 6 = 0
factor
(z - 1)(z - 6) = 0
z = 1, z = 6
.
2007-06-07 20:46:33
·
answer #6
·
answered by Robert L 7
·
0⤊
0⤋
first, transpose 56z-48 to the other side:
8z^2-56z+48=0
then factor:
(4z-4)(2z-12)=0
4z-4=0
4z=4
z=1
2z-12=0
2z=12
z=6
2007-06-07 20:53:55
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋